Pengaruh Penerapan Modernisasi Administrasi Perpajakan terhadap Kepatuhan Wajib Pajak - Junaedi Abdillah; Eti Suprihatin (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study has a purpose to find out how the influence of the application of administrative modernization in taxation on taxpayer compliance in. The method used in this study is descriptive research method with case study approach. The purpose of descriptive method is to systematically describe facts, objects or subjects as they are. It aims to systematically describe the facts and characteristics of the object under investigation appropriately. Data and information gathering was carried out by field study through questionnaire as a research tool distributed to Taxpayers registered and Account Representative who served in A Region. The result of this study is the application of modernization of tax administration has an influence on taxpayer compliance level, while the rest is influenced by other factors outside the study. Hypothesis test results obtained that Ho rejected and Ha accepted, thus the hypothesis that the authors proposed that Application of modernization in taxation has a significant influence on taxpayer compliance in A Regiom.